2011
DOI: 10.1080/08854726.2011.616166
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of Chaplaincy Care

Abstract: The current article reviews the research conducted in the United States on the clinical practice of chaplains with patients and family members, referrals to chaplains, patient satisfaction with chaplaincy services, and the limited literature on the efficacy of chaplain interventions. It also discusses the methodological limitations of studies conducted on these topics and makes suggestions for improving future chaplaincy research. The authors conclude that past studies have not adequately defined chaplain inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 110 publications
0
43
0
Order By: Relevance
“…Attending to the spiritual needs of patients has begun to be formally recognized by professional spiritual care providers, health care councils, and regulatory agencies such as the Joint Commission, the National Consensus Project Guidelines for Quality Palliative Care, palliative care clinicians, and health care delivery systems over the past 30 years. However, research on spiritual care and chaplaincy care is in its infancy, as chaplains, humanities scholars, and empirical researchers have yet to generate widely accepted research‐based definitions of spirituality, spiritual care, and chaplaincy practice that could be used in studies of outcome and efficacy . Existing research into the core elements of oncology spiritual care programs has shown that organizational and institutional issues are significant, often underrecognized factors in the success of such programs.…”
Section: Spiritual Carementioning
confidence: 99%
“…Attending to the spiritual needs of patients has begun to be formally recognized by professional spiritual care providers, health care councils, and regulatory agencies such as the Joint Commission, the National Consensus Project Guidelines for Quality Palliative Care, palliative care clinicians, and health care delivery systems over the past 30 years. However, research on spiritual care and chaplaincy care is in its infancy, as chaplains, humanities scholars, and empirical researchers have yet to generate widely accepted research‐based definitions of spirituality, spiritual care, and chaplaincy practice that could be used in studies of outcome and efficacy . Existing research into the core elements of oncology spiritual care programs has shown that organizational and institutional issues are significant, often underrecognized factors in the success of such programs.…”
Section: Spiritual Carementioning
confidence: 99%
“…A significant proportion of faith leaders consider faith healing or pastoral counseling an appropriate and fully adequate way to treat serious mental illness because it focuses on the “whole person” (Leavey et al, 2007). The efficacy of these approaches to “treating” individuals with mental illness is unknown because of the lack of empirical research in this area (Jankowski, Handzo, & Flannelly, 2011). However, one study finds that a pastoral intervention designed to treat depression and conducted by ordained ministers with some chaplaincy training was associated with decreased depressive symptoms in a retirement community sample (Baker, 2001).…”
Section: Challenges In Partnerships With Fbosmentioning
confidence: 99%
“…However, even tools with "assessment" in their name may be more appropriately termed spiritual screening tools (Borneman et al, 2010). Such screens do help identify the need for a professional Shields et al chaplain and can lead to appropriate referrals from other healthcare providers (Jankowski et al, 2011).…”
Section: Spiritual Assessment Vs Spiritual Screeningmentioning
confidence: 99%